Penataan Nusa Tenggara pada masa kolonial 1915-1950 - Ardhana, I. Ketut; Paath, Peusy Sharmaya Intan (Jakarta : Divisi Buku Perguruan Tinggi, Raja Grafindo Persada, 2005)
History on small Sunda Island, Nusa Tenggara Timur during Dutch kolonial, 1915-1950
Bibliografi : p. 457-501 and index
Translation from Germany
Keywords: Nusa Tenggara Timur (Indonesia) -- Politics and government; Sunda Islands, lesser (Indonesia) -- History and criticism; Indonesia -- Politics and government